IMPLEMENTASI PEMASARAN HIJAU MELALUI PENAWARAN TAS BELANJA ECO-BAG UNTUK MENINGKATKAN LOYALITAS PELANGGAN PASAR SWALAYAN - Putra, Andika Djunaidi; Suprapti, Ni Wayan Sri (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 11 Nomor 1 Tahun 2017, 2017)
Supermarket is one of the business units that cause of the environmental polluted, especially in problem of plastic waste. To reduce this problem, the management of many giant supermarkets offers eco-bag to their customers as implementation of green marketing. This study is conducted in Denpasar City and Badung Regency. The objective of this study is to explain the influence of product quality of eco-bag on customer loyalty, with eco-bag perceived value as a mediating variable. Data are collected by questionaire from 105 customers of five supermarkets. Data are analyzed by path analysis and Sobel test. The study found that the product quality of eco-bag is positively influence on customer loyalty, and eco-bag perceived value is significantly mediated the effect of product quality of eco-bag on customer loyalty.
Keywords: product quality of eco-bag, perceived value, customer loyalty